The library book [large type] - Orlean, Susan (Thorndike Press large print popular and narrative nonfiction., 2018)
On the morning of April 29, 1986, a fire alarm sounded in the Los Angeles Public Library. As the moments passed, patrons and staff outside of the building realized this was not the usual fire alarm. As one fireman recounted, "Once that first stack got going, it was 'Goodbye, Charlie.'" The fire was disastrous, reaching 2000 degrees and burning for more than seven hours. It consumed four hundred thousand books and damaged seven hundred thousand more. More than thirty years later, the mystery remains: Did someone purposefully set fire to the library -- and if so, who? Susan Orlean chronicles the LAPL fire and its aftermath to showcase the larger, crucial role that libraries play in our lives; delves into the evolution of libraries across the country and around the world, from their humble beginnings as a metropolitan charitable initiative to their current status as a cornerstone of national identity; brings each department of the library to vivid life through on-the-ground reporting; studies arson and attempts to burn a copy of a book herself; reflects on her own experiences in libraries; and reexamines the case of Harry Peak, the blond-haired actor long suspected of setting fire to the LAPL more than thirty years ago. Along the way, Orlean introduces us to an unforgettable cast of characters from libraries past and present -- from Mary Foy, who in 1880 at eighteen years old was named the head of the Los Angeles Public Library at a time when men still dominated the role, to Dr. C.J.K. Jones, a pastor, citrus farmer, and polymath known as "The Human Encyclopedia" who roamed the library dispensing information; from Charles Lummis, a wildly eccentric journalist and adventurer who was determined to make the L.A. library one of the best in the world, to the current staff, who do heroic work every day to ensure that their institution remains a vital part of the city it serves.